Pengaruh Kompensasi dan Pengembangan Karir terhadap Kepuasan Kerja Pegawai Kantor Otoritas Jasa Keungan - Nur Mayang Suri; Suharini Suharini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In this era of rapid development, the business world must be very selective in selecting competitive human resources. This makes the company very concerned about the job satisfaction of its employees, because good employee job satisfaction can be beneficial for the company itself. This research aims to test and analyze the effect of compensation and career development on job satisfaction of employees of the Financial Services Authority Office. The method of data collection in this study was carried out by distributing questionnaires to 60 respondents of the Financial Services Authority employees. The research method used is quantitative method with sampling technique, namely saturated sample. The data used are primary data and secondary data. The results of this research indicate that Compensation has a positive and significant effect on Job Satisfaction.